Clinical Presentation of Abdominal Tuberculosis - Putranto, Agi S.; Bakti, Purnama S.; Mazni, Yarman; Jeo, Wifanto S.; Lalisang, Toar JM. (The New Ropanasuri Journal of Surgery, 2018)
Introduction. Nowadays, tuberculosis remains an issue of global. It may have affected all gastrointestinal organs, including peritoneum. Thus, diagnostic approach of this abdominal tuberculosis remains challenging as it may present non–specific features and mimics other abdominal pathologies. A study focused on clinical and laboratory findings, imaging and evaluation of management of those diagnosed as abdominal tuberculosis was required. Method. A cross–sectional study proceeded retrospectively aimed for an evaluation. All abdominal tuberculosis managed in dr Cipto Mangunkusumo General Hospital, Jakarta and Fatmawati General Hospital, Jakarta during January 2011 to December 2013 were enrolled. Data collected from data registration, subject’s characteristic, clinical findings, laboratory findings, and imaging were variables subjected to analysis. Results. There were forty–eight subjects recorded. The most symptoms found were abdominal pain (81.25%), abdominal distention (72.9%), fever (68.75%) and weight loss (68.75%). While as most laboratory findings were leukocytosis (52%) and elevated erythrocyte sedimentation rate, ESR (72.9%). And up to 50% subject showed normal chest x–ray while as other showed non–specific features for pulmonary tuberculosis. Conclusion. Clinical presentations showed to be diverse. Laboratory finding, and imaging maybe valuable to diagnose abdominal tuberculosis, although chest x–ray represents non–specific features for pulmonary tuberculosis. Evaluation of these clinical findings and lead to accurate diagnostic approach; which was determine the characteristics associated with abdominal tuberculosis diagnostics value..